Schindler's list - Spielberg, Steven (Quezon City : Magnavision, 2000)
Schndler's List, a Steven Spielberg film, is a cinematic masterpiece that has become one of the most honoured films of all time. Winners of seven Academy Awards, including Best Picture and Best Director, it also won every ,major Best Picture Award and an exceptional number of additional honours. Among them were seven British Academy Awards; the Best Picture Awards from the New York Dilm Critics Circle, the National Society of Film Critics, the National Board of Review, the Producers Guild, the Los Anglese Film Critics, the Chicago, Boston, and Dallas Film Critics; a Christopher Award; and the Hollywood Foreign Press Association Golden Globe Awards. Steven Spielberg was further honoured with the Directors Guild of American Award. The film presents the indelible true story of the enigmatic Oskar Schindler, a member of the Nazi Party, womanizer and war profiteer who saved the lives of more than 1,100 Jews during the Holocaust. It is the trimph of one man who made a difference, and the drama of those who survived one of the darkest chapters in human history because of what he did. Directed by Steven Spielberg, the film which also won Academy Awards for Sreenplay, Cinemotography, Music, Editing, and Art Direction, Stars an acclaimed cast headed by Liam Neeson, Ben Kingsley, Raplh Fiennes, Caroline Goodall, Jonathan Sagalle, and Embeth Davidtz.